Graphic cigarette package warning labels: investigating the effectiveness of graphic images among new and occasional smokers - Dieterich, Sara E., author; Henry, Kimberly, advisor; Harman, Jennifer, committee member; Long, Marilee, committee member (Colorado State University. Libraries, 2012)
Smoking is a major public health concern. As a result of recent legislation, cigarette manufacturers will soon be required to display graphic pictorial depictions of the health consequences of tobacco on all products sold in the U.S. Research has shown that fear appeal messages can be effective for health behavior change, but little research has examined the effects of graphic imagery in warning messages. The present study explored the effectiveness of graphic and non-graphic cigarette package warning labels and examined potential mediating processes among occasional and recently initiating smokers. No significant direct effects of the graphic warning labels (as compared to non-graphic labels) on explicit attitudes, implicit attitudes, and intentions to not smoke were found. The results also show that graphic warning labels were associated with increased perceived personal relevance and negative affective reactions compared to non-graphic warning labels. Personal relevance was also found to mediate the relationship between warning label condition and negative implicit attitudes. Implications for prevention are discussed.